2022
DOI: 10.1007/s12185-022-03406-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of specialized cell cycles during erythroid lineage development: insights from single-cell RNA sequencing

Abstract: Early erythroid progenitors known as CFU-e undergo multiple self-renewal cell cycles. The CFU-e developmental stage ends with the onset of erythroid terminal differentiation (ETD). The transition from CFU-e to ETD is a critical cell fate decision that determines erythropoietic rate. Here we review recent insights into the regulation of this transition, garnered from flow cytometric and single-cell RNA sequencing studies. We find that the CFU-e/ETD transition is a rapid S phase-dependent transcriptional switch.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The downregulation of genes involved in the cell cycle in SUPT5H-edited cells led us to ask whether the cell cycle is altered in SUPT5H-edited cells during the transition from progenitors to precursors. Consistent with previous studies describing cell cycle remodeling during murine erythropoiesis (Socolovsky 2022;Hwang et al 2017), we observed a rapid increase in the Sphase cell population, and a reciprocal decrease in the G0/G1 population, in control cells (Figure 5A-B). By contrast, in SUPT5H-edited cells, we observed a prolonged shift in cell cycle dynamics with a higher percentage of cells in G0/G1 (58±2% vs 45±3%) and a lower percentage in S (39±1% vs 52±2%) relative to control cells (Figure 5A-C, S5D).…”
Section: Perturbing Supt5h Causes Stage-specific Changes In the Cell ...supporting
confidence: 92%
“…The downregulation of genes involved in the cell cycle in SUPT5H-edited cells led us to ask whether the cell cycle is altered in SUPT5H-edited cells during the transition from progenitors to precursors. Consistent with previous studies describing cell cycle remodeling during murine erythropoiesis (Socolovsky 2022;Hwang et al 2017), we observed a rapid increase in the Sphase cell population, and a reciprocal decrease in the G0/G1 population, in control cells (Figure 5A-B). By contrast, in SUPT5H-edited cells, we observed a prolonged shift in cell cycle dynamics with a higher percentage of cells in G0/G1 (58±2% vs 45±3%) and a lower percentage in S (39±1% vs 52±2%) relative to control cells (Figure 5A-C, S5D).…”
Section: Perturbing Supt5h Causes Stage-specific Changes In the Cell ...supporting
confidence: 92%
“…We filtered this dataset to remove non-erythroid contaminants, then re-clustered the data (Figure 1A) and identified clusters via surface markers and transcription factors differentially expressed throughout erythropoiesis (Supplemental Figure 1; Figure 1C). Committed erythroid progenitors (BFU-E, CFU-E, and proerythroblasts) are transcriptionally distinct from erythroid precursors 52 . Surprisingly, we found that erythroid progenitors express antigen presentation machinery that is typically restricted to professional antigen presenting immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Two broad progenitor categories exist: earlier progenitors that form ’bursts’ (the burst-forming-unit-erythroid, ’BFU-e’) and later progenitors that give rise to smaller colonies (colony-forming-unit-erythroid, ’CFU-e’). The progenitor phase is followed by erythroid terminal differentiation (ETD), a phase in which morphologically-identifiable erythroblasts (also known as erythroid precursors) undergo three to five maturational cell divisions, culminating in enucleation and the formation of immature red blood cells (reticulocytes) [2].…”
Section: Identifying Progenitors Undergoing a Key Transcriptional Swi...mentioning
confidence: 99%